PENGARUH SIKAP KEUANGAN DAN PERILAKU KEUANGAN TERHADAP LITERASI KEUANGAN - Wilda Rahmayanti; Hanifa Sri Nuryani; Abdul Salam (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2019)
This study aims to examine the effect of financial attitude and financial behavior on financial literacy (case study on the housewives in the Lito Village, Moyo Hulu Subdistrict, Sumbawa District). This research is a quantitative research with a causal method. The method of data collection was done by distributing questionnaires to 125 respondents, namely the housewives in the Lito Village, Moyo Hulu Subdistrict, Sumbawa Regency. The sampling technique uses purposive sampling. Data analysis used is multiple linear regression analysis. Based on the results of the study it can be concluded that financial attitudes a significant positive effect on financial literacy with a value of 4.382> 1,657 and a significance level (?) 0,000 <0.05, financial behavior has a significant positive effect on financial literacy with a value of 5,060> 1,657 and a significance level (?) of 0,000 <0.05 and the level of financial literacy of housewives is very high 98.4% (>76%).